High-parameter phenotypic characterization reveals a subset of human Th17 cells that preferentially produce IL-17 against M. tuberculosis antigen - Paul Ogongo; Paul Ogongo; Anthony Tran; Florence Marzan; David Gingrich; Melissa Krone; Francesca Aweeka; Cecilia S. Lindestam Arlehamn; Jeffrey N. Martin; Steven G. Deeks; Peter W. Hunt; Joel D. Ernst (Frontiers in Immunology, 2024)
BackgroundInterleukin-17–producing CD4 T cells contribute to the control of Mycobacterium tuberculosis (Mtb) infection in humans; whether infection with human immunodeficiency virus (HIV) disproportionately affects distinct Th17-cell subsets that respond to Mtb is incompletely defined.MethodsWe performed high-definition characterization of circulating Mtb-specific Th17 cells by spectral flow cytometry in people with latent TB and treated HIV (HIV-ART). We also measured kynurenine pathway activity by liquid chromatography-mass spectrometry (LC/MS) on plasma and tested the hypothesis that tryptophan catabolism influences Th17-cell frequencies in this context.ResultsWe identified two subsets of Th17 cells: subset 1 defined as CD4+Vα7.2−CD161+CD26+and subset 2 defined as CD4+Vα7.2−CCR6+CXCR3−cells of which subset 1 was significantly reduced in latent tuberculosis infection (LTBI) with HIV-ART, yet Mtb-responsive IL-17–producing CD4 T cells were preserved; we found that IL-17–producing CD4 T cells dominate the response to Mtb antigen but not cytomegalovirus (CMV) antigen or staphylococcal enterotoxin B (SEB), and tryptophan catabolism negatively correlates with both subset 1 and subset 2 Th17-cell frequencies.ConclusionsWe found differential effects of ART-suppressed HIV on distinct subsets of Th17 cells, that IL-17–producing CD4 T cells dominate responses to Mtb but not CMV antigen or SEB, and that kynurenine pathway activity is associated with decreases of circulating Th17 cells that may contribute to tuberculosis immunity.